2006
DOI: 10.1093/jat/30.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Metaxalone in Human Plasma by Liquid Chromatography Coupled to Tandem Mass Spectrometry

Abstract: A simple, rapid, sensitive, and selective liquid chromatography-tandem mass spectrometry (MS) method was developed and validated for the quantification of metaxalone, a skeletal muscle relaxant, in human plasma using galantamine as internal standard (IS). Following liquid-liquid extraction, the analytes were separated using an isocratic mobile phase on a reverse phase C18 column and analyzed by MS in the multiple reaction monitoring mode using the respective [M+H]+ ions, m/z 222/161 for metaxalone and m/z 288/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Metaxalone (MTX), a 2-oxazolidinone derivative (5-(3, 5-dimethylphenoxymethyl)-2-oxazolidinone) with skeletal muscle relaxant activity [1,2] is shown in Figure 1. Analytical methods using RP-HPLC [3,4]; liquid chromatography mass spectrometry (LC-MS/MS) [5][6][7] and ultra-violet (UV) spectroscopy [8,9] has been successfully reported for MTX quantification. However, none of them adopt systematic statistical optimization; rather those methods pursued traditional approach i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Metaxalone (MTX), a 2-oxazolidinone derivative (5-(3, 5-dimethylphenoxymethyl)-2-oxazolidinone) with skeletal muscle relaxant activity [1,2] is shown in Figure 1. Analytical methods using RP-HPLC [3,4]; liquid chromatography mass spectrometry (LC-MS/MS) [5][6][7] and ultra-violet (UV) spectroscopy [8,9] has been successfully reported for MTX quantification. However, none of them adopt systematic statistical optimization; rather those methods pursued traditional approach i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Savard et al reported a tedious liquid-liquid extraction method of metaxalone using LC-MS/MS technique but complete validation data were unavailable to support method application [9]. Nirogi et al also reported liquid-liquid extraction technique to determine metaxalone in plasma by using LC-MS/MS principle, yet matrix effect using hemolyzed and lipemic plasma and stability of metaxalone in blood remained un-addressed during validation performance [10]. Moreover, there is no reported method where metaxalone recovery was achieved higher than 75% to the best of knowledge of authors.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reported methods for DIC include UV-spectroscopic methods [3–6], RP-HPLC methods [7–10] and LC-MS method [11]. For MET the reported methods are UV-Spectroscopic method [12], RP-HPLC method [13, 14] and LC-MS method [15]. Only one RP-HPLC method has been reported so far for simultaneous estimation of both the drugs [16], but the reported method is not stability-indicating in nature.…”
Section: Introductionmentioning
confidence: 99%